The Center for Creative Leadership handbook of coaching in organizations - Riddle, Douglas Duane Jacobs, 1949-; Hoole, Emily R., 1968-; Gullette, Elizabeth C. D., 1969- (San Francisco, CA : Jossey-Bass, A Wiley Brand, 2015)
"From coaching superiors to coaching business teams, this book outlines the Center for Creative Leadership (CCL) approach to professional coaching to help readers better manage leadership development and talent management program outcomes. With expert guidance on the key functions of human resources, learning and development, and organizational development, readers will gain insight into the issues associated with coaching program implementation and management, and the use of internal versus external coaches. Coverage includes a wide range of coaching-based services used in most large organizations, with practical advice on creating the right programs for maximum impact within the available budget." --
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Executive coaching; Leadership; Mentoring in business; Employees -- Coaching of; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Employees -- Coaching of; Executive coaching; Leadership; Mentoring in business; Electronic books